Diversity of traditional medicinal plants in silvipastoral land use systems of Indian North Western Himalaya - Swaran Lata
The Indian Himalayan Region (IHR) is one of the world$1 (Bs mega biodiversity hotspots with diverse landscapes. The IHR harbour diverse agro-ecological conditions known for its silvipastoral land use systems for conservation and management of biodiversity. The present study highlights the diversity of ethno-medicinal plants in silvipastoral land use systems of Himachal Pradesh, North Western Himalaya along with their indigenous medicinal uses. The study was conducted using semi-structured interviews with locals and Vaidya$1 (Bs through participatory rural appraisal exercises, in 12 districts of study region spanning across 4 agroclimatic zones. The study identified 201 species belonging to 73 families and 170 genera. Fabaceae followed by Lamiaceae, Rosaceae, Poaceae were the dominant families. The study identified utilization of 197 angiosperm species, 3 gymnosperms and 2 pteridophyte species. The species diversity showed maximum distribution of herbs (83), followed by trees (58) and shrubs (48). Leaves and root were the most frequently used part followed by fruits, whole plant, tuber and seeds. Powder followed by paste, juice, decoction, and extracts were the frequently utilized preparation methods for ethnomedicinal preparation for treatment of various ailments. Further the study attempts to address threat categories and suggests conservation and management strategies for potential ethnomedicinal plants.s